A Phase I and Pharmacokinetic Study of Lapatinib in Combination with Letrozole in Patients with Advanced Cancer - Chu, Quincy S.C.; Cianfrocca, Mary E.; Goldstein, Lori J.; Gale, Meg; Murray, Nicholas; Loftiss, Jill; Arya, Nikita; Koch, Kevin M.; Pandite, Lini; Fleming, Ronald A.; Paul, Elaine; Rowinsky, Eric K. (Clinical cancer research, 2008)
Purpose: The main objectives of this phase I and pharmacokinetic, open-label study were to determine the optimally tolerated regimen (OTR), safety, pharmacokinetics, and clinical activity of lapatinib in combination with letrozole in patients with advanced solid malignancies. Experimental Design: Patients with advanced breast cancer with immunohistochemically detectable estrogen or progesterone receptors or other cancers were eligible. Doses of lapatinib were escalated in cohorts of three subjects from 1,250 to a maximum of 1,500 mg/d based on dose-limiting toxicities in the first treatment cycle. The letrozole dose was fixed at 2.5 mg/d. Additional patients were enrolled at the OTR dose level to further evaluate safety and for pharmacokinetic analyses. Results: Thirty-nine patients were enrolled in the study: 12 in the dose-escalation group, 7 in the OTR safety group, and 20 in the pharmacokinetic group. The OTR dose level was identified as 1,500 mg/d lapatinib and 2.5 mg/d letrozole. The most common (>25% of patients) drug-related adverse events were diarrhea (77%), rash (62%), nausea (46%), and fatigue (26%). No significant differences were observed in the pharmacokinetic variables ( C max and AUC) of lapatinib and letrozole when coadministered compared with single-agent administration. One patient with endometrial cancer had a confirmed partial response. Conclusions: Clinically relevant doses of lapatinib in combination with letrozole were well tolerated and did not result in a pharmacokinetic interaction, and clinical antitumor activity was observed.